Pengaruh Latihan Uphill Running terhadap Kecepatan dan Akselerasi Atlet Sprinter di UKM Atletik Universitas Negeri Surabaya - Dina Resti Wardhani; Bhekti Lestari (Mutiara Pendidikan dan Olahraga, 2025)
Sprint or short-distance running is a running event in the sport of athletics that demands maximum speed in a short amount of time. Speed and acceleration are key factors in achieving success in sprint events, making effective training methods essential to enhance athlete performance. This study aims to determine the effect of uphill running training on the speed and acceleration of sprinter athletes in the Athletics Student Activity Unit (UKM) at Universitas Negeri Surabaya. The research uses a quantitative method with a pre-experimental design, specifically the One-Group Pretest-Posttest. The sampling technique used is purposive sampling, with a population of 24 athletes and a sample of 15 male sprinter athletes aged 18-21 years. The instrument used was a 60-meter and 30-meter sprint test, with uphill running training conducted over 6 weeks at a frequency of three times per week. The results showed a significant improvement in the athletes' speed and acceleration after undergoing uphill running training, as evidenced by the t-test results with a significance value of <0.05. Therefore, it can be concluded that uphill running training can positively influence the speed and acceleration of sprinter athletes in the UKM athletics program at Universitas Negeri Surabaya.